Clusterization of patients with idiopathic pulmonary fibrosis with chemokine receptors: a possible role in the diagnostic work-up of idiopathic pulmonary fibrosis? - Brunetti, Giuseppe; Malovini, Alberto; Testoni, Claudia; Bellazzi, Riccardo; Balestrino, Antonella; Meriggi, Antonio; Moscato, Gianna; Alessandrini, Arnaldo; Rivolta, Federica; Pignatti, Patrizia (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background and objective: Idiopathic pulmonary fibrosis (IPF) is a chronic and irreversible interstitial lung disease whose diagnosis often requires surgical lung biopsies (SLB) in cases without consistent radiological findings. We previously published that the expression of the chemokine receptors CXCR3 and CCR4 on T cells is significantly different in bronchoalveolar lavage (BAL) of IPF patients from other interstitial lung diseases. The aim of the study was to evaluate cut-off  values of CXCR3 and CCR4 receptors expressed on bronchoalveolar lavage (BAL) and peripheral blood (PB) T cells  useful for a differential diagnosis. Methods: Ninety-three patients were enrolled: 35 IPF, 36 interstitial lung diseases (nIPF) and 22 sarcoidosis. CXCR3 and CCR4 were evaluated on BAL and PB T lymphocytes with flow cytometry. Results: Among PB and BAL variables considered, the values of the ratio of BAL and PB CXCR3 on CD4 cells were clustered in the most informative way to obtain a classification rule for the diagnosis of patients without steroid therapy (n = 66/93).  Patients with a CXCR3 ratio BAL/PB on CD4 T cells lower or equal than 1.43 were assigned to the IPF group with sensitivity = 0.87 and specificity = 0.90.  All the other variables considered showed lower sensitivity and specificity in discriminating IPF patients. Conclusions: The evaluation of chemokine receptors on BAL and PB T lymphocytes could aid to discriminate IPF in subjects without steroid therapy, particularly in those patients with a high-resolution computed tomography (HRCT)  non typical for Usual Interstitial Pneumonia (UIP).